All aboard the relationship between board composition and the firm performance of ASEAN firms - Banaag, Andrew Joseph R.; Bisuña, Vincent Paolo B.; Daway-Ducanes, Sarah Lynne S. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
For any firm, a board of directors’ main goal is that of separation of ownership and control, allowing for the integration of controls that mitigate principal-agent problems. This study seeks to ascertain the effects of board structure variables, namely: CEO duality, the number of independent directors, the number of women in the board, and board size on Tobin’s Q, a measure of firm performance. Bloomberg data on 155 firms from 5 ASEAN member states, namely, the Philippines, Singapore, Indonesia, Malaysia, and Vietnam were collected. Using Blundell-Bond’s (1998) and Windmeijer’s (2005) two-step System Generalized Method-of-Moments (System-GMM) model, the results show that certain aspects of board structure affect Tobin’s Q. The number of independent board members has a significantly positive effect (at the 1% level) on Tobin’s Q. In contrast, CEO duality and the number of women on the board, both pose significant negative effects on firm performance. Across industries, CEO duality negatively affects Tobin’s Q. CEO Duality in the Manufacturing and Services industries stand out as being significantly negative at the 5% level, whereas the Banking & Finance and Real Estate industries are significantly negative at the 10% level.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Corporations -- Southeast Asia; Affiliated corporartions -- Southeast Asia; Southeast Asia